2007
DOI: 10.1111/j.1471-0528.2007.01291.x
|View full text |Cite|
|
Sign up to set email alerts
|

Is laparoscopically assisted radical vaginal hysterectomy for cervical carcinoma safe? A case control study with follow up

Abstract: Objective To compare a new surgical approach, laparoscopically assisted radical vaginal hysterectomy (LARVH) with open radical hysterectomy in women with cervical cancer. Can selected women benefit from the minimally invasive approach without compromising safety (recurrence rate) and morbidity (complications)?Design Retrospective case control study.Setting A tertiary referral unit for gynaecological malignancies.Population Thirty women undergoing LARVH were included and compared with 30 women undergoing open r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
26
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 21 publications
2
26
1
1
Order By: Relevance
“…In this study, both LARVH and RH appeared equally efficacious in the treatment of early-stage cervical cancer with no recurrences in either group, in contrast to other published data [17,18]. The two procedures carry similar complication rates but with a different pattern of problems following each.…”
Section: Discussioncontrasting
confidence: 53%
“…In this study, both LARVH and RH appeared equally efficacious in the treatment of early-stage cervical cancer with no recurrences in either group, in contrast to other published data [17,18]. The two procedures carry similar complication rates but with a different pattern of problems following each.…”
Section: Discussioncontrasting
confidence: 53%
“…Studies on the efficacy of the TLRH plus pelvic lymph node dissection for the treatment of the early cervical cancer indicated TLRH has the advantage of small trauma and less bleeding, faster postoperative recovery over the tradition abdominal radical hysterectomy (ARH) [6][7][8][9] . A retrospective analysis of 60 patients with early cervical cancer conducted by Zakashansky et al [10] showed that in this cohort, no conversion to laparotomy appeared; the intraoperative blood loss was only 200 mL, far less than 520 mL in ARH; there was no intraoperative blood transfusion compared to 5 cases (5/30) of intraoperative blood transfusion in laparotomy; the average hospital stay in TRLH was 1.8 days, shorter than that in ARH; however, the operative time lasted 318.5 min in TRLH, significantly longer than 242.5 min in ARH.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, studies have shown that the TLRH plus pelvic lymph node dissection possesses more advantages than traditional laparotomy, such as small trauma, less bleeding, quick recovery [5][6] . However, as the laparoscopic surgery is technically challenging and may cause many complications, the feasibility and safety of the laparoscopic approach are warranted for more investigations [7][8] . This study retrospectively analyzed the data of 110 patients with cervical cancer or endometrial cancer who underwent TLRH plus pelvic lymph node dissection in a period of 15 months with an attempt to examine the short-term efficacy and application value of the surgical procedure for the treatment of uterine malignant tumors.…”
mentioning
confidence: 99%
“…Research has shown that laparoscopic radical hysterectomy is feasible and safe and induces less trauma due to less intraoperative bleeding, less postoperative pain, a shorter period of recovery and a shorter hospital stay, while the number of lymph nodes removed was almost equal to that shown in conventional open surgery (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Laparoscopically assisted vaginal hysterectomy has become the preferred approach for cervical cancer treatment.…”
Section: Discussionmentioning
confidence: 99%